Cloning in the news : an analysis of how the science and ethics of cloning are reported in three daily newspapers of Cape Town - Van der Linden, Cornelis Albert (Stellenbosch : Stellenbosch University, 2012)
Thesis (MPhil) -- Stellenbosch University, 2004.